THE INTERCULTURAL COMPETENCE. DEVELOPING EFFECTIVE INTERCULTURAL COMMUNICATION SKILLS (Konferensiyalar | Conferences, 2024)
Today, effective intercultural communication is crucial due to the increasing significance of understanding the world's cultural diversity. Factors such as immigration, urbanization, international employment, exchange programs, and easy travel have led to frequent interactions between people from diverse cultural backgrounds. This paper aims to emphasize the importance of cultivating attitudes and communication skills essential for multicultural interactions, both in everyday life and within organizations. Acquiring knowledge about other cultures and honing intercultural communication competencies can ease multicultural encounters and foster greater openness and tolerance towards others.